Oxygen requirements in relation to sludge age in wastewater treatment plants. Issue 1 (November 2021) - Kemmou, Liana; Samiotis, Georgios; Amanatidou, Elisavet
Abstract: Sustainability of activated sludge (AS) wastewater treatment processes is inexplicably linked to minimization of secondary wastes, such as waste sludge, as well as energy requirements for achieving effluent quality standards. Oxygen requirements and waste sludge management accounts for most of energy consumption in aerobic AS wastewater treatment plants (WWTPs). In this study, a novel, highly aerobic AS process, entitled complete solids retention AS process (CRAS), is being evaluated in terms of waste sludge production and biomass oxygen utilization rate. Aim of this work is to study the effect of solids retention time (SRT) on observed sludge yields and on oxygen requirements for respiration in order to evaluate CRAS process as a sustainable alternative to typical activated sludge processes.